The Molecular Dialog between Flowering Plant Reproductive Partners Defined by SNP-Informed RNA-Sequencing. Issue 5 (11th April 2017) - Leydon, Alexander R.; Weinreb, Caleb; Venable, Elena; Reinders, Anke; Ward, John M.; Johnson, Mark A.
Abstract : Pollen- and pistil-specific patterns of gene expression were defined during Arabidopsis reproduction using single nucleotide polymorphism-informed RNA-seq analysis. Abstract: The molecular interactions between reproductive cells are critical for determining whether sexual reproduction between individuals results in fertilization and can result in barriers to interspecific hybridization. However, it is a challenge to define the complete molecular exchange between reproductive partners because parents contribute to a complex mixture of cells during reproduction. We unambiguously defined male- and female-specific patterns of gene expression during Arabidopsis thaliana reproduction using single nucleotide polymorphism-informed RNA-sequencing analysis. Importantly, we defined the repertoire of pollen tube-secreted proteins controlled by a group of MYB transcription factors that are required for sperm release from the pollen tube to the female gametes, a critical barrier to interspecific hybridization. Our work defines the pollen tube gene products that respond to the pistil and are required for reproductive success; moreover, we find that these genes are highly evolutionarily plastic both at the level of coding sequence and expression across A. thaliana accessions.